Delegated portfolio management: a survey of the theoretical literature - Livio Stracca (European Central Bank (ECB), 2005)
This paper provides a selective review of the theoretical literature on delegated portfolio management as a principal-agent relationship. The main focus of the paper is to review the analytical issues raised by the peculiar nature of the delegated portfolio management relationship within the broader class of principalagent models. In particular, the paper discusses the performance of linear vs. nonlinear compensation contracts in a single-period setting, the possible effects of limited liability of portfolio managers, the role of reputational concerns in a multiperiod framework, and the incentives to noise trading. In addition, the paper deals with some general equilibrium dimensions and asset pricing implications of delegated portfolio management. The paper also suggests some directions for future research.
Keywords: D82; G11; 330; adverse selection; agency; Delegated portfolio management; Moral Hazard; principal-agent models; Portfolio-Management; Prinzipal-Agent-Theorie; Adverse Selektion; Moral Hazard